A influência da fadiga nos músculos eversores durante a entorse lateral do tornozelo - Rodrigues, Karina Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The inversion and plantar flexion ankle sprain is one of the most common injuries that occur in daily life activities and sports. Although acute symptoms can be resolved quickly, many people report persistent pain and instability. This type of injury often occurs in the final phase of a training or competition, and even though the sprain is multifactorial, such particularity provides the establishment of a relationship between the event sprain and fatigue. In this view, the present study aims to analyze the latency and activation intensity of the brevis and longus peroneus muscles in conditions of fatigue and also compare individuals with stability and instability of the ankle. For this purpose it was initially developed a simulated platform sprains in inversion and plantar flexion, in which both feet of the volunteers were fixed and below where rested his feet were coupled force transducers, one on each side. The study included 23 female volunteers, physically active, separated into two groups: 11 were part of the group stability, had no injury history in the joint complex of the ankle in the last 12 months and another 12 in functional instability group, classified by Cumberland Questionnaire Ankle Instability Tool. To induce fatigue, it was initially recorded a Contraction Isometric Maximal Voluntary (MVIC) in eversion and plantar flexion. During the induction, the participants were instructed to maintain 70% of the MVIC. At the time the force applied was below 60% of the MVIC the protocol was interrupted and the volunteers placed in standing position on the simulator platform. Before and after fatigue were held ten simulations sprain bilaterally randomly and simultaneously to record the electromyographic signal. Thus, it was observed that after the fatigue did not change the latency, but there was a reduction of muscle contraction level, evidenced by the reduction in amplitude of the electromyographic signal. Still, there were no noticeable differences between the groups stability and instability and there was a higher activity of the peroneus brevis compared to longus. Therefore, it was concluded that the local neuromuscular control was compromised in fatigue situations, due to reduced activity level of the peroneus longus and brevis muscles. Moreover, it was not possible to observe difference in muscle behavior between stable and unstable functionally ankles.

A entorse do tornozelo em inversão e flexão plantar é uma das lesões mais comuns que ocorrem nas atividades de vida diária e no esporte. Embora os sintomas agudos possam se resolver rapidamente, muitos indivíduos relatam persistência de dor e instabilidade. Este tipo de lesão frequentemente acontece na fase final de um treino ou competição, e mesmo sabendo que a entorse é multifatorial, tal particularidade propicia estabelecer uma relação entre o evento da entorse e a fadiga. Diante disto, o presente estudo propõe analisar a latência e a intensidade de ativação dos músculos fibulares curto e longo em condições de fadiga, e ainda comparar indivíduos com estabilidade e instabilidade do tornozelo. Para esse fim, inicialmente foi desenvolvida uma plataforma simuladora da entorse em inversão e flexão plantar, na qual ambos os pés das voluntárias foram fixados e abaixo de onde se apoiava os pés foram acoplados transdutores de força, um de cada lado. Participaram do estudo 23 voluntárias do sexo feminino, fisicamente ativas, separadas em dois grupos: 11 fizeram parte do grupo estabilidade, não apresentavam histórico de lesão no complexo articular do tornozelo nos últimos 12 meses e outras 12 no grupo instabilidade funcional, classificadas pelo Questionário Cumberland Ankle Instability Tool. Para indução da fadiga, inicialmente foi registrada a Contração Isométrica Voluntária Máxima (CIVM) em eversão e flexão plantar. Durante a indução as voluntárias foram orientadas a manter 70% da CIVM. No momento em que a força aplicada fosse menor que 60% da CIVM o protocolo era interrompido e as voluntárias posicionadas em ortostatismo sobre a plataforma simuladora. Antes e após a fadiga foram realizadas dez simulações da entorse bilateralmente de forma randomizada e simultaneamente com o registro do sinal eletromiográfico. Assim, foi possível observar que após a fadiga não houve alteração da latência, no entanto ocorreu uma redução do nível de contração muscular, constatada pela diminuição da amplitude do sinal eletromiográfico. Ainda, não foram notadas diferenças entre os grupos estabilidade e instabilidade e verificouse maior atividade do músculo fibular curto quando comparado ao longo. Portanto, pôde-se concluir que o controle neuromuscular local ficou comprometido em situações de fadiga, devido à redução do nível de atividade dos músculos fibular longo e curto. Além disso, não foi possível observar diferença no comportamento muscular entre tornozelos estáveis e funcionalmente instáveis.
The influence of fatigue in everter muscles during lateral ankle sprain
Keywords: Muscle fatigue; Ankle sprain; Chronic ankle instability; Electromyography; Fadiga muscular; Entorse de tornozelo; Instabilidade crônica do tornozelo; Eletromiografia